Teacher’s Strategy to Overcome the Learning Plateau in Early Childhood Learning - Clara Shinta Wijayanti; Waharjani Waharjani; Wantini Wantini (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2023)
An indicator of learning success relates to the teacher’s skills in carrying out various learning methods suitable for children. This study analyzed the teacher's strategy to overcome the learning plateau in early childhood learning. The method used is a systematic literature review. The data analysis technique was to analyze research findings, draw judgments, interpretations and draw conclusions based on the relevance of research findings that were systematically selected with research themes from the literature. The results showed that the learning plateau could be overcome by various methods, namely a) Outing class, b) Total Physical Response (TPR), c) Storytelling and d) Inquiry. In particular, each method has a purpose and focus on a particular field. The four methods used in research are continuously able to complete early childhood readiness in forming logical thinking and mental readiness and these methods become a reference so that children become more creative, active, and able to find a lot of learning in a broad and real way, not only in their environment. school but also outside of school.